Which Individual Characteristics Mediate the Relationship Between Social Entrepreneurial Passion and Social Entrepreneurial Intention? - Harianto, Eric; Bernardus, Denny; Murwani, Fulgentius Danardana; Jatiwiwaha, Marcellino Priyana; Jatiperwira, Stefan Yudana; Effendi, Laij Victor (Journal of Ecohumanism, 2024)
Social entrepreneurship, operationalized through social entrepreneurial behavior, focuses on social missions, primarily looking for new solutions to social problems. Social entrepreneurial intention, however, is the main foundation before the emergence of social entrepreneurial behavior. This research examines a model of social entrepreneurial intention empirically tested on undergraduate students involved in innovative business projects. Specifically, this study aims to test the positive relationship between social entrepreneurial passion and social entrepreneurial intention and verify which individual characteristics (i.e., social entrepreneurial self-efficacy, pro-social behavior, and social support) mediate the positive relationship between social entrepreneurial passion and social entrepreneurial intention. The data was collected from 416 undergraduate students and analyzed using the confirmatory factor analysis and Hayes’s PROCESS macro approach. The results showed that social entrepreneurial self-efficacy, pro-social behavior, and social support completely mediated the positive relationship between social entrepreneurial passion and social entrepreneurial intention. This study provides theoretical implications for extending the literature regarding the theory of planned behavior in the context of social entrepreneurship. This study also has practical consequences for entrepreneurship educators and policymakers in educational management.